Tumor containing fragment number influences immunohistochemistry positive rate of HER2 in biopsy specimens of gastric cancer - Chen Xu; Yalan Liu; Xiaowen Ge; Dongxian Jiang; Ying Zhang; Yuan Ji; Jun Hou; Jie Huang; Jieakesu Su; Haiying Zeng; Jing Qin; Yingyong Hou (BMC, 2017)
Abstract Background HER2 assessment in biopsy specimens of gastric cancer (GC) is challenging because of the intratumoral heterogeneity. False negative results may be get because of limited biopsy material. The aim of this study is to explore how tumor-containing fragment number and biopsy specimen number affect HER2 immunohistochemistry (IHC) positive rate. Methods Eight hundred and ninety biopsy specimens and 459 paired resected specimens were collected. IHC staining of HER2 was performed. HER2 IHC positive (scored 3+) rate was compared based on tumor-containing fragment number, biopsy specimen number, average size and tumor tissue proportion of tumor-containing fragments. The positive predictability of biopsy specimens to resected specimens was analyzed based on tumor fragment number. Results HER2 IHC positive rates were 2.0, 3.5, 7.0, 13.2, 17.1, and 15.9% when tumor fragment numbers were 1, 2, 3, 4, 5 and 6 respectively. The rate rose with the increase of tumor fragment number (P = 0.004). ROC curve analysis showed that biopsy specimens exhibited positive predictability when tumor fragment number reached 3, but showed better performance when the number was ≥4 (P < 0.05). After fragment number reached 4, no statistic differences were reached in either HER2 IHC positive rate or positive predictability with further increase of the number (P > 0.05). HER2 IHC positive rate was not associated with biopsy number (P = 0.127), average size of tumor fragments (P = 0.397), and tumor tissue proportion of tumor fragments (P = 0.825) directly. Conclusions The number of tumor-containing fragments influences HER2 IHC positive (scored 3+) rate. Greater than or equal to 4 (≥4) tumor fragments give better results in the positive rate as well as positive predictability. We recommend the number of tumor containing fragments be described in the HER2 IHC pathology reports for clinical reference in endoscopic biopsy specimens of GC.